Development of Entrepreneurial Skills Among Engineering Students - Diószeginé Zentay, Éva (International Journal of Engineering and Management Sciences, 2018)
Education is the major contributor to the development of culture, including entrepreneurial culture as well. The aim of this study is to demonstrate the characteristics of a successful entrepreneur and how can be developed the initiative and entrepreneurial competence through education. The task of the education is to help young people develop qualities that are the basis of entrepreneurship. Such is creativity, initiative, responsibility, risk-taking and independence.